Development of a Bio-Composite Interlocking Block System for River Revetment - Alias, Nor Azlina (2006)
In Malaysia, many types of revetment systems are used in channel lining. These systems are mostly manufactured and patented overseas or designed using technologies transferred from foreign countries. Development of an interlocking block with environmental consideration is a new approach that may help in river protection and restoration. It is important to design and develop locally a new revetment block which is economical, durable and environmentally friendly.